Peningkatan Kapasitas Digital Marketing UMKM Melalui Pendampingan Komprehensif di Wilayah Wonocolo - Rahila Amanatul Ummah (PASAI : Jurnal Pengabdian kepada Masyarakat, 2025)
This community service initiative aims to enhance the economic independence of Micro, Small, and Medium Enterprises (MSMEs) in Wonocolo District, Surabaya, through digital branding assistance and utilization of online marketing platforms. The primary challenges faced by MSMEs in the digital era include low literacy and skills in optimally using various online marketing channels.​ The activities were implemented using a Participatory Action Research (PAR) approach, encompassing observation, planning, action, and reflection stages, ensuring active involvement of MSME actors in every change process. Comprehensive assistance was provided through four main stages: (1) business registration on Google Maps/Google Business Profile to boost local visibility and consumer trust, (2) creation and management of ShopeeFood accounts as sales channels to expand market reach, (3) facilitation of QRIS (Quick Response Code Indonesian Standard) registration to simplify non-cash transactions, and (4) socialization and practice of effective online marketing strategies, including social media utilization and digital promotional content.​ Through this series of assistance, partner MSMEs gained improved understanding and practical skills in digital marketing and digital financial services, evidenced by their ability to manage business profiles on digital platforms, leverage online marketplaces/food delivery services, and accept non-cash payments via QRIS. Thus, the program is expected to impact increased business visibility, market expansion, and revenue growth, thereby strengthening the competitiveness and economic independence of MSMEs in Wonocolo amid digital transformation.